VARIED CHANGES IN MANGA KYOU KARA ORE WA!! INTO THE DRAMA VERSION - Pamungkas, Wahyu Aji; Febrianty, Fenny (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Varied changes in the process of ecranisation are common when adapting a literary work into a visual format such as film in an effort to adapt the story to the new medium. This study aims to describe the form of ecranisation in the form of varied changes sourced from manga. The benefit of this research lies in its contribution to understanding the process of ecranisation and this study provides insights into how literary works are transformed into visual formats and how storytelling is adapted to suit different mediums. The research method used is qualitative descriptive method. By analyzing the specific changes that occurred in the transition from manga to television, the recency of this research highlights the evolving nature of storytelling techniques and audience preferences in modern visual media. The data sources in this research are the manga Kyou Kara Ore Wa!! by Hiroyuki Nishimori and the Television Drama Series Kyou Kara Ore Wa!! directed by Fukuda Yuichi. The results of this study show that there are changes that have occurred in the manga to the drama series version. The changes focus on the varied changes that occur in the setting.